Dynamic Activity of miR-125b and miR-93 during Murine Neural Stem Cell Differentiation In Vitro and in the Subventricular Zone Neurogenic Niche. - Annalisa Lattanzi; Bernhard Gentner; Daniela Corno; Tiziano Di Tomaso; Pieter Mestdagh; Frank Speleman; Luigi Naldini; Angela Gritti (PLoS ONE)
Several microRNAs (miRNAs) that are either specifically enriched or highly expressed in neurons and glia have been described, but the identification of miRNAs modulating neural stem cell (NSC) biology remains elusive. In this study, we exploited high throughput miRNA expression profiling to identify candidate miRNAs enriched in NSC/early progenitors derived from the murine subventricular zone (SVZ). Then, we used lentiviral miRNA sensor vectors (LV.miRT) to monitor the activity of shortlisted miRNAs with cellular and temporal resolution during NSC differentiation, taking advantage of in vitro and in vivo models that recapitulate physiological neurogenesis and gliogenesis and using known neuronal- and glial-specific miRNAs as reference. The LV.miRT platform allowed us monitoring endogenous miRNA activity in low represented cell populations within a bulk culture or within the complexity of CNS tissue, with high sensitivity and specificity. In this way we validated and extended previous results on the neuronal-specific miR-124 and the astroglial-specific miR-23a. Importantly, we describe for the first time a cell type- and differentiation stage-specific modulation of miR-93 and miR-125b in SVZ-derived NSC cultures and in the SVZ neurogenic niche in vivo, suggesting key roles of these miRNAs in regulating NSC function.